Web-based training management system - Hasmin, Isahak; Hirman, Sidi; Muhammad Faharul Hilme, Bakar; Sani, Songli (Universiti Malaysia Sarawak, UNIMAS, 2003)
Industrial training program is a compulsory course in Faculty of Information Technology, UNIMAS. It is very good to have in any university as it's putting students to the real situation of works. Besides that, industrial training also used to promote companies do not know what do students do in Faculty in Information Technology. If it is promoted then company will know. But, problems encounter when large volume of students applied.